The correlation between solidification rates, microstructure integrity and tensile plastic behaviour in 4.2 wt.% silicon strengthened ductile iron - Angella, Giuliano; Taloni, Marcello; Donnini, Riccardo; Zanardi, Franco (AGH University of Science and Technology Press, 2022)
High Silicon Strengthened Ductile Iron (HSiSDI) with 4.2 wt.% of silicon was produced in Y-blocks with different thicknesses to investigate the effects of the solidification rate on microstructure integrity and tensile mechanical properties. With decreasing solidification rates, the graphite degeneracy with the appearance of chunky graphite became more significant at the highest silicon contents, so chemical ordering and graphite degeneracy seemed to be qualitative explanations of tensile property degradation. However, a deeper analysis of the relationship between solidification rate, microstructure and tensile properties was realized through an innovative approach based on the Matrix Assessment Diagram (MAD), where the parameters of Voce equation resulting from best-fitting the experimental tensile flow curves of a significant number of HSiSDI samples, were plotted. For 3.5 wt.% silicon content, the MAD analysis indicated that the microstructure was sound for any solidification rate, while for 4.5 wt.% the microstructure was sound only for the fastest solidification rates. For 4.2 wt.% silicon content the MAD analysis pointed out that the tensile plastic behaviour and the microstructure integrity was in between the 3.5 and 4.5 wt.% silicon contents, representing a composition threshold where the reliable microstructures were only found with the fastest solidification rates, while considerable variability was found for the slowest ones. Support to the MAD analysis results was given from microstructure observations.
Journal of Casting & Materials Engineering
Bibliogr. s. 5-7.
Keywords: strain hardening; constitutive equations; integrity assessment; ductile irons; high silicon content